Perturbation of kinetochore function using GFP-binding protein in fission yeast. Issue 11 (16th August 2021) - Deng, Da-Jie; Xia, Qian-Cheng; Jia, Guo-Song; Suo, Fang; Chen, Jia-Li; Sun, Li; Wang, Jin-Qing; Wang, Shuang-Min; Du, Li-Lin; Wang, Yamei; Jin, Quan-Wen
Abstract: Using genetic mutations to study protein functions in vivo is a central paradigm of modern biology. Single-domain camelid antibodies generated against GFP have been engineered as nanobodies or GFP-binding proteins (GBPs) that can bind GFP as well as some GFP variants with high affinity and selectivity. In this study, we have used GBP-mCherry fusion protein as a tool to perturb the natural functions of a few kinetochore proteins in the fission yeast Schizosaccharomyces pombe . We found that cells simultaneously expressing GBP-mCherry and the GFP-tagged inner kinetochore protein Cnp1 are sensitive to high temperature and microtubule drug thiabendazole (TBZ). In addition, kinetochore-targeted GBP-mCherry by a few major kinetochore proteins with GFP tags causes defects in faithful chromosome segregation. Thus, this setting compromises the functions of kinetochores and renders cells to behave like conditional mutants. Our study highlights the potential of using GBP as a general tool to perturb the function of some GFP-tagged proteins in vivo with the objective of understanding their functional relevance to certain physiological processes, not only in yeasts, but also potentially in other model systems.